Jít vlastní cestou - Goins, Jeff (Portál, 2019)
The search begins with passion but does not end there. Only when our interests connect with the needs of the world do we begin living for a larger purpose. Those who experience this intersection experience something exceptional and enviable. Though it is rare, such a life is attainable by anyone brave enough to try. Goins explains how to abandon the status quo and live a life that matters with true passion and purpose.